Pengaruh Pembelajaran Melalui Program TVRI Terhadap Aspek Psikomotorik Siswa SD di Masa Pandemi Covid-19 - Eva Luthfi Fakhru Ahsani; Ayu Ningsih (AR-RIAYAH : Jurnal Pendidikan Dasar, 2020)
The learning program through the TVRI program can make it easier for students who have obstacles to access the internet, due to economic reasons and geographic location. This study aims to examine the effect of learning from home through TVRI on the psychomotor aspects of elementary school students during the spread of Covid-19. There are 3 levels studied, namely readiness, guidance, and basic skills. The method used in this research is descriptive qualitative. The research subjects included students in grades III, IV, and V SDN Jambean 02. The data filling technique was an instrument in the form of observation and structured interviews. Learning from home through the TVRI learning program guided by parents or adults, affects the psychomotor aspects of students at the readiness and guidance stages, but at the basic skilled stage it has not been successful. This shows the role of teachers in schools cannot be saved by technology, even when students study at home accompanied by parents. With the learning from home through the TVRI program, it is hoped that parents can read students when studying, with the aim of developing students' psychomotor aspects optimally